Towards Adequate Housing: An Analysis of Renta Joven (Peru) and the Housing Rental Pool (Spain) - Hernández Huamán, Lesly Katerine (2024)
The purpose of this article is to carry out a comparative analysis between the social housing programs Renta Joven in Peru and the Bolsa de Vivienda de Alquiler in Barcelona, Spain. Through an exhaustive study of the problematic situation, the theoretical framework, and the characteristics of both programs, the results and limitations in meeting the housing needs of their respective beneficiaries are evaluated. The work is based on a qualitative approach, based on documentary review and critical analysis of primary and secondary sources. Likewise, throughout the article, the criticisms associated with each program are explored and recommendations are formulated to improve their effectiveness. Finally, conclusions are presented that seek to contribute to the improvement of social policies in the area of social housing.